EVALUATION OF THE EFFECTIVENESS OF ELECTRONIC AUDITING SYSTEMS IN BANKS AND THEIR IMPACT ON THE DETECTION OF FINANCIAL CORRUPTION - Mohammad Abdulwahid Jayyas (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study aims to evaluate the effectiveness of electronic auditing systems in Iraqi banks and their contribution to uncovering financial corruption, given the economic crises and regulatory pressures facing the country. With rising rates of financial corruption and the growing need to enhance transparency and accountability, it has become imperative to develop effective electronic oversight systems within banking institutions. Method: The study relied on an analysis of financial data and banking indicators for the period (2019–2022). Results: The results concluded that electronic auditing systems represent an effective oversight tool that has contributed to improving financial performance indicators, such as capital growth, net profits, and increased revenues. It also demonstrated the ability of these systems to detect financial violations early, reduce resource manipulation, and mitigate the misuse of credit facilities. However, the study revealed a number of challenges hindering the full implementation of electronic auditing systems, most notably weak digital infrastructure, high operating costs, and the lack of qualified specialist personnel. Novelty: The study recommended expanding the application of electronic auditing systems, modernising the technological infrastructure, investing in human resource development, enhancing integration between banks and regulatory bodies, and developing performance indicators to measure the effectiveness of these systems on a sustainable basis.